Analysis of genomic differences among Clostridium botulinum type A1 strains - Fang, Ping-Ke (BioMed Central, 2010)
BACKGROUND: Type A1 Clostridium botulinum strains are a group of Gram-positive, spore-forming anaerobic bacteria that produce a genetically, biochemically, and biophysically indistinguishable 150 kD protein that causes botulism. The genomes of three type A1 C. botulinum strains have been sequenced and show a high degree of synteny. The purpose of this study was to characterize differences among these genomes and compare these differentiating features with two additional unsequenced strains used in previous studies. RESULTS: Several strategies were deployed in this report. First, University of Massachusetts Dartmouth laboratory Hall strain (UMASS strain) neurotoxin gene was amplified by PCR and sequenced; its sequence was aligned with the published ATCC 3502 Sanger Institute Hall strain and Allergan Hall strain neurotoxin gene regions. Sequence alignment showed that there was a synonymous single nucleotide polymorphism (SNP) in the region encoding the heavy chain between Allergan strain and ATCC 3502 and UMASS strains. Second, comparative genomic hybridization (CGH) demonstrated that the UMASS strain and a strain expected to be derived from ATCC 3502 in the Centers for Disease Control and Prevention (CDC) laboratory (ATCC 3502*) differed in gene content compared to the ATCC 3502 genome sequence published by the Sanger Institute. Third, alignment of the three sequenced C. botulinum type A1 strain genomes revealed the presence of four comparable blocks. Strains ATCC 3502 and ATCC 19397 share the same genome organization, while the organization of the blocks in strain Hall were switched. Lastly, PCR was designed to identify UMASS and ATCC 3502* strain genome organizations. The PCR results indicated that UMASS strain belonged to Hall type and ATCC 3502* strain was identical to ATCC 3502 (Sanger Institute) type. CONCLUSIONS: Taken together, C. botulinum type A1 strains including Sanger Institute ATCC 3502, ATCC 3502*, ATCC 19397, Hall, Allergan, and UMASS strains demonstrate differences at the level of the neurotoxin gene sequence, in gene content, and in genome arrangement.